Joint Union-Management Job Evaluation in the Canadian Steel Industry - Bean, Ronald (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1962)
Summary While a Teaching Fellow in Political Economy at McMaster University in 1961, Mr. Bean prepared this article which is an empirical study of the application of a C. W. S. system in evaluating jobs in the Canadian Steel Industry.